The Role of Instagram Social Media as a Marketing Communication Strategy in the Era of Digital Transformation of the Banking Industry - Ayu Agustriana, Renny (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
Especially in the financial sector, social media plays an important role in managing marketing communications strategies in this era of digitalization. This study aims to analyze how the role of the use of Instagram social media on marketing communication strategies that can be applied by the banking industry. This study employs a comprehensive approach, utilizing literature analysis and the Systematic Literature Review (SLR) methodology. A total of 128 Scopus articles were meticulously identified through the Publish or Perish platform, supplemented by the utilization of Mendeley and Vosviewer applications. Subsequently, these articles were refined to 96 journal articles deemed pertinent for in-depth descriptive analysis. The results illuminate the potential for banks to capitalize on various social media functionalities, including photo uploads, fostering account popularity, and employing targeted advertising, as viable strategies to attain their marketing objectives. With the right approach, banks can increase consumer engagement, increasingly global market reach and Brand image is stronger through social media. The implications of this research include practical guidance for banking practitioners in designing successful marketing communication strategies in this digital age, as well as contributions to the development of knowledge in the field of marketing and social media. Thus, this research provides valuable insights for the banking industry and leads to more research that will help understand how social media plays a role in banking marketing.